Effect of Multiple Reflow on IMC Formation using Various Surface Finishes - Siti Rabiatull Aisha, Idris; Ali, Ourdjini (Inderscience Enterprises Ltd., 2013)
In this paper, the results of a study on the effect of multiple reflow on the mechanism of intermetallic compounds (IMCs) formation of solder joints made from lead–free Sn–4Ag–0.5Cu (SAC405) on electroless nickel/electroless palladium/immersion gold (ENEPIG), electroless nickel/immersion gold (ENIG), immersion silver (ImAg) and copper surface finishes are presented. After the first reflow soldering, the well–known intermetallic Cu6Sn5 was observed in ImAg and Copper of surface finishes. While for ENEPIG and ENIG, mainly, (Ni,Cu)3Sn4 and (Cu,Ni)6Sn5 was formed respectively. By increasing the number of reflows up to three, the thickness of intermetallics increased gradually and their grain sizes coarsened. The intermetallics growth kinetics showed that the interfacial phase Cu6Sn5, (Ni,Cu)3Sn4 and (Cu,Ni)6Sn5 was controlled mainly by grain boundary diffusion and that the intermetallic growth on ENEPIG was found to be slowest among other surface finishes being used.